Pengaruh Rasio ROA, EPS, CR, DER Dan TATO Terhadap Harga Saham Subsektor Perbankan Yang Terdaftar Pada Bursa Efek Indonesia Tahun 2019 – 2023 - Pandu Dwi Anggoro; Nova Anggrainie (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
The development of the country's economy cannot be separated from the banking sector because banks are intermediary institutions that collect and channel funds from the public for the development of a country. This study aims to analyze the effect of Return On Assets, Earning Per Share, Current Ratio, Debt to Equity Ratio and Total Asset Turnover on the share price of banking subsector companies listed on the IDX for the 2019-2023 period. The data collection method is the documentation method. The data used is secondary data and the sampling technique uses purposive sampling technique with a total sample of 26 companies. The analytical tools used are Descriptive Statistical Analysis, Classical Assumption Test, Multiple Linear Regression, t test, F test and Coefficient of Determination. The data in this study were processed using SPSS. The results showed that Return On Assets, Earning Per Share and Total Asset Turnover partially affect stock prices, while Current Ratio and Debt to Equity Ratio do not partially affect stock prices. Return On Assets, Earning Per Share, Current Ratio, Debt to Equity Ratio and Total Asset Turnover affect stock prices in banking subsector companies simultaneously